Faktor Kegagalan Mediasi dalam Penyelesaian Perkara Perceraian di Pengadilan Agama (Studi Kasus Di Pengadilan Agama Yogyakarta Kelas 1A Tahun 2022) - Khairunnisa, Ayudya; Anisa Salsabila; Ahmad Prayozi Sugandi (TERAJU: Jurnal Syariah dan Hukum, 2023)
This article examines the factors that caused the failure of the mediation process in resolving divorce cases handled at the Yogyakarta Religious Court. The aim of this research is to determine the level of success of the divorce mediation process and determine the elements that hinder the success of the divorce mediation process at the Yogyakarta Religious Court. This research uses research methods from various literature review sources such as various journal articles. Based on the research results, it shows that the success rate of the divorce mediation process at the Yogyakarta Religious Court is classified as very low, which shows that the implementation of the divorce mediation process at the Yogyakarta Religious Court has not been effective in reducing the high number of divorce cases. The inhibiting elements include: Both parties have a strong desire and determination to divorce, the presence of bad faith on the part of the parties, the absence of one or both parties involved in the mediation process, the limited number of mediator judges, the lack of the mediator's ability to carrying out the mediation process, and there are also conflicts that are very complicated and there is no hope that they can be repaired again. Keywords: Mediation, Divorce, Religiouns Courts.